Outcomes of Capsular Dissection Technique with Use of Bipolar Electrocautery in Total Thyroidectomy: A Rural Tertiary Center Experience - Das, Amal T. (J Clin Diagn Res, 2016)
INTRODUCTION: Total thyroidectomy is one of the most routinely performed head and neck surgical procedures with extremely low mortality. This procedure has been associated with two major complications such as recurrent laryngeal nerve injury and hypocalcaemia due to parathyroid insufficiency. The use of bipolar electrocautery has not been widely accepted in view of thermal damage to adjacent structures. AIM: To study the outcomes and complications of capsular dissection technique along with use of bipolar electrocautery in total thyroidectomy. MATERIALS AND METHODS: The study was conducted from May 2013 to May 2016. The study was performed at Department of ENT Otorhinolayngology, DM WIMS Hospital, Wayanad, Kerala, India. This retrospective descriptive study analysed the outcome of 130 patients who underwent total thyroidectomy by capsular dissection technique along with use of bipolar electrocautery for cauterization of vascular pedicles, at our institution over a 3 year period. RESULTS: The incidence of permanent unilateral vocal cord palsy was 1.5% and permanent hypocalcaemia was 2.3%. There was no case of haemorrhage or haematoma in this study. CONCLUSION: Total thyroidectomy by capsular dissection technique along with the use of bipolar electrocautery has very low incidence of recurrent laryngeal nerve and parathyroid injury, as per our data. Hence, we recommend this technique along with routine use of bipolar electrocautery for total thyroidectomy.